Strong ethics and flexible actions, the properties of traditional ecological knowledge (TEK), as key resources for socioecological resilience to the impacts of climate change: a case study of Baojiatun, Yunnan-Guizhou Plateau karst area, southwest China - Jing Li; Feng Han (Ecology and Society, 2022)
This paper explores how indigenous people rely on traditional ecological knowledge (TEK) as a means to adapt to climate change. We focus on the observation, interpretation, and adaptation of natural phenomena among farmers from Baojiatun in the karst depression of central Guizhou, where the Han people have settled for more than 600 yr. First, the farmers are culturally rooted in ethics of nature worship and ancestor reverence, forming a community that is sensitive to natural phenomena and governed by local rules and regulations. Second, TEK has a special use in that the indigenous people are not worried about climate change itself because they view their own knowledge system as sufficient to aid adaptation. Third, the properties of TEK are critical resources for socioecological resilience to the impacts of climate change, including a keen observation of phenological change, local indicators for recognizing these changes, and a willingness to abandon certain assumptions as needed in response to changes. This paper suggests that TEK plays an important role in socioecological resilience, because it encourages indigenous people's sensitivity to change and provides an adaptable knowledge system with a strong ecocentric view of nature that can support adjustments and that is flexible enough to accommodate the adjustments needed to respond to changes. The findings of this paper highlight the important role of TEK in fragile ecosystems under global climate change.